Challenges of Treatment-Resistant Bipolar Depression in the Elderly: A Case Study of Successful Modafinil Augmentation - Arinze Mbanusi; Muhammad-Kazim Kanani (BJPsych Open)
Aims: Bipolar depression remains a major therapeutic challenge, particularly in elderly populations where treatment options are constrained by comorbidities and medication tolerability. Despite pharmacological advancements, many patients experience persistent depressive symptoms, even after multiple trials of mood stabilizers, antipsychotics, and antidepressants. Lithium, while effective, is associated with nephrotoxicity, limiting its use in the elderly. Modafinil, a wakefulness-promoting agent primarily used for narcolepsy, has emerged as a potential adjunctive treatment for treatment-resistant bipolar depression (TRBD). Its broad neurochemical effects, targeting multiple pathways, suggest promise in addressing refractory mood symptoms. However, its role in elderly patients remains underexplored.